Robot-assisted versus conventional laparoscopic radical prostatectomy: a systematic review and meta-analysis of randomised controlled trials - Haney, Caelán Max; Kowalewski, Karl-Friedrich; Westhoff, Niklas Christian; Holze, Sigrun; Checcuci, Enrico; Neuberger, Manuel; Haapiainen, Henry; Egen, Luisa; Antti, Kaipia; Porpiglia, Francesco; Stolzenburg, Jens-Uwe (European urology focus, 2023)
Context - Robot-assisted radical prostatectomy (RARP) has largely replaced conventional laparoscopic radical prostatectomy (LRP) even though the costs are significantly higher. Justification for this change is the hope for better postoperative functional results because of better dissection of the neurovascular bundle. - Objective - To perform a systematic review and meta-analysis of randomised controlled trials (RCTs) comparing RARP and LRP for the primary outcome of continence (use of 0 pads or 1 safety pad) at 12 mo after surgery. - Evidence acquisition - We searched the CENTRAL, MEDLINE, and Web of Science databases for RCTs comparing RARP versus LRP for adults with localised prostate cancer (PC). Where possible, individual-patient data were obtained. Secondary outcomes were potency for patients potent at baseline; a trifecta of patients continent and potent and no recurrence/further treatment; positive surgical margins; biochemical recurrence; and further treatment for PC. The systematic review was registered prospectively (reviewregistry1190 on www.researchregistry.com/). - Evidence synthesis - Five RCTs were identified. Three trial teams provided data. For another trial, only published data were available. The fifth trial was terminated prematurely because of insufficient recruitment and thus could not be included. Overall, data for 1205 randomised patients were available. At 12 mo, there was no significant difference between the two groups regarding continence (odds ratio [OR] 1.95, 95% confidence interval [CI] 0.67-5.62). However, at 3 mo and 6 mo there were significant differences in favour of RARP. Significantly more patients who were potent at baseline and underwent a robot-assisted nerve-sparing approach were potent at 12 mo (OR 4.05, 95% CI 1.63-10.09). - Conclusion - At 12 mo after surgery there are no differences in continence between RARP and LRP. Short-term continence benefits of RARP were observed. Potent patients undergoing RARP consistently show better potency postoperatively. - Patient summary - We analysed differences between robot-assisted removal of the prostate and conventional keyhole surgery for removal of the prostate. At 12 mo after surgery, there were no differences in continence outcomes between the two approaches. However, patients who were potent at baseline and underwent robot-assisted surgery were more likely to be potent at 12 mo.
Online verfügbar: 21. Juni 2023, Artikelversion: 15. Dezember 2023
Gesehen am 04.04.2024